2016
DOI: 10.4081/gh.2016.492
|View full text |Cite
|
Sign up to set email alerts
|

Predominance and geo-mapping of avian influenza H5N1 in poultry sectors in Egypt

Abstract: Highly pathogenic avian influenza (HPAI) virus of the H5N1 subtype has been enzootic in the Egyptian poultry with significant human infections since 2008. This work evaluates the epidemiological and virological information from February 2006 to May 2015 in spatial and temporal terms. Only data with confirmed HPAI H5N1 sub-type were collected, and matched with the epidemiological data from various spatially and temporally-dispersed surveillances implemented between 2006 and 2015. Spatio-temporal analysis was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 15 publications
(19 reference statements)
4
27
0
Order By: Relevance
“…Furthermore, increasing the standards of cleanliness as well as containment when applied reduces or prevent the risk of introducing disease into a flock and hence mortality [67,[77][78][79][80][81]. A recent study conducted by Arafa et al [82] and Arafa et al [83] showed that epidemiological dynamics of HPAI has changed with the origins of majority of outbreaks. This points toward household poultry, and it is associated with human cases of H5N1 infections.…”
Section: Poultry Husbandry Methods and Multispecies Livestock Farmingmentioning
confidence: 99%
“…Furthermore, increasing the standards of cleanliness as well as containment when applied reduces or prevent the risk of introducing disease into a flock and hence mortality [67,[77][78][79][80][81]. A recent study conducted by Arafa et al [82] and Arafa et al [83] showed that epidemiological dynamics of HPAI has changed with the origins of majority of outbreaks. This points toward household poultry, and it is associated with human cases of H5N1 infections.…”
Section: Poultry Husbandry Methods and Multispecies Livestock Farmingmentioning
confidence: 99%
“…In commercial farms and backyards, the incidence of HPAI H5N1 virus in Lower Egypt was higher than that in Upper Egypt (Aly et al, 2008. The higher incidence rate of disease was observed in the Nile Delta region where there are high densities of poultry and human populations (Arafa et al, 2016, El-Zoghby et al, 2013.…”
Section: Study Areamentioning
confidence: 94%
“…This study was carried out in five Nile Delta governorates (Sharkia, Qalyobia, Menofia, and Gharbia) of Egypt as highlighted in figure 2, where the higher numbers of disease outbreaks were reported (Arafa et al, 2016). In addition, these regions are considered as leading poultry producing governorates in Egypt (ElMasry et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Another study reported the confirmation of H5N1 from quails on farms (0.2%) and in LBMs (0.8%) (Arafa et al 2016b). Quails have been reported to be an important mixing vessel for AIVs due to the expression of receptors for mammalian and avian AIVs on their epithelial cell surfaces (Nguyen et al 2016;Thontiravong et al 2012).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 98%